Answer:
Step-by-step explanation:
The equation is <span>f(x) = 2x5 - 9x4 + 12x3 - 12x2 + 10x - 3 = 0
remark:
the sum of coefficients is = 2-9+12-12+10-3=-7+7=0, so a=1 is a zero of f
f can be written as </span>f(x) = (x-1)Q(x), and f(x) / (x-1)= Q(x)
after euclid's division
Q(x) = 2x4 - 7x3 + 5x2 - 7x +3
so for finding the other roots, making Q(x) for product of factors is a must
Answer:
Step-by-step explanation:
As per Janayda,
From the figure attached,
In ΔTRQ,
m∠TRQ + m∠RQT + m∠QTR = 180°
25° + m∠RQT + 35° = 180°
m∠RQT = 180° - 60°
m∠RQT = 120°
Since, m∠RQT + m∠PQT = 180° [Linear pair of angles]
m∠PQT = 180° - m∠RQT
= 180° - 120°
= 60°
In right angled triangle TPQ,
m∠TPQ + m∠PQT + m∠PTQ = 180°
90° + 60° + m∠PTQ = 180°
m∠PTQ = 180° - 150°
= 30°
Similarly, other angles can also be evaluated from the given information.
In ΔQTP and ΔNTP,
TP ≅ TP [Reflexive property]
NP ≅ PQ [Given]
ΔQTP ≅ ΔNTP [By LL postulate for congruence]
Therefore, Janayda is correct.
While Sirr is incorrect.
Since, there is not the enough information to prove ΔRTQ and ΔMTN equal, Isabelle is incorrect.
The answer is 11.2 which means 11 1/5